Environmental and health impact of solid waste management activities - Hester, R. E.; Harrison, Roy M., 1948- (Issues in environmental science and technology ;, 2002)
Solid waste management issues are a highly emotive topic. Disposal costs need to be balanced against environmental impact, which often results in heated public debate. Disposal options such as incineration and landfill, whilst unpopular with both the public and environmental pressure groups, do not pose the same environmental and health risks as, for example, recycling plants. This book, written by international experts, discusses the various waste disposal options that are available (landfill, incineration, composting, recycling) and then reviews their impact on the environment, and particularly on human health. Comprehensive and highly topical, Environmental and Health Impact of Solid Waste Management Activities will make a strong contribution to scientific knowledge in the area, and will be of value to scientists and policy-makers in particular.